Voter Turnout and New Forms of Political Participation of Young People: A Comparative Analysis Between Chile and Spain [Abstención Política y Nuevas Formas de Participación Política de Los Jóvenes: Análisis Comparativo Entre Chile y España] - Sola-Morales, S (University of La Laguna, 2017)
Introduction. The objective of this research is to explore the relationship between the voter turnout and the new forms of participation of young Chileans and Spaniards, as well their perception about politics and the forms of participation which seem most relevant to them. Methodology. In order to do this, a comparative analysis between the two countries, with a sample of 928 university students between the ages of 18 and 24 is realized. Results. The data showed some distrust of the current democratic system. Additionally, while voter turnout decreases in Chile and Spain, other unconventional - offline and online-political activities increase. Conclusions. Definitively, young people are seeking greater participation as citizens in political affairs. Likewise, although many students use social networks as channels to keep abreast of the activities of politicians, this use is still low compared to that of other public figures. © 2017, University of La Laguna. All rights reserved.